Visual Identity Design of Nabilla Sulam Usus South Lampung - Nadya Naura Rahmaisya; Muhammad Redintan Justin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2026)
One of Lampung’s cultural heritage elements that deserves preservation is sulam usus, a unique embroidery technique with high historical and aesthetic value. In this context, visual identity design plays a crucial role as an effective communication tool that conveys cultural values to a broader audience. The purpose of this study is to design the visual identity of Nabilla Sulam Usus as a branding strategy to enhance brand awareness of Lampung’s traditional crafts, particularly sulam usus. The design methods employed in this study include observation, interviews with the business owner, literature review, and SWOT analysis. The design elements developed comprise logo, color scheme, typography, and visual applications across primary and secondary media, such as packaging, brochures, and social media content. The findings of this project indicate that a strong and coherent visual identity reflecting traditional values can build a professional and appealing brand image. This is expected to strengthen Nabilla Sulam Usus’s position in both local and international markets while contributing to the preservation of cultural heritage through visual communication approaches.